Lemierre syndrome leading to ankylosis of the temporomandibular joint. Issue 10 (December 2019) - Johnson King, O.; Sharma, V.
Abstract: Lemierre syndrome, also known as Lemierre's disease is a rare condition that was first described by Andre Lemierre in 1936. We present a case of a 3-year-old boy who presented with ankylosis of the right temporomandibular joint (TMJ) secondary to a mastoid infection as part of Lemierre syndrome. His ankylosis resulted in restricted mouth opening, which had a considerable impact on his speech and ability to eat. Surgical treatment comprising right coronoidectomy, gap arthroplasty of the TMJ, and interpositional fat grafting, enabled him to move his jaw and function has returned. This case report highlights the consequences of Lemierre syndrome and the need for clinicians to be aware of its features and the impact it may have on patients.